Hubungan Kualitas Pelayanan Kesehatan Dengan Tingkat Kepuasan Pasien Poliklinik Rawat Jalan HIV/AIDS Rumah Sakit Umum Daerah Djasamen Saragih Tahun 2023 - Dearmalina Sariyunita Saragih; Sri Rezeki (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Based on WHO data shows that 5.7 to 8.4 million people die due to poor quality health services each year in low and middle income countries, which represent up to 15% of total deaths in this country. Patients in conditions requiring health care die 60% due to poor service quality and 40% of deaths due to lack of utilization of the health service system, especially in low and middle income countries (WHO, 2020). This study aims to identify the relationship between the quality of health services and the level of patient satisfaction at the HIV/AIDS Outpatient Polyclinic at the Djasamen Saragih Regional General Hospital in 2023. Type of quantitative research with cross sectional design. This research was conducted on a sample of 41 midwives. To measure the characteristics of respondents used a data collection form, to measure the quality of service with the level of satisfaction of respondents used a questionnaire. Based on the relationship between the quality of health services and the level of patient satisfaction, a p-value of 0.000 (p <0.05) was obtained which indicated that there was a significant relationship between the characteristics of midwives, such as the relationship between the quality of health services and the level of patient satisfaction at the HIV/AIDS Outpatient Polyclinic at Home Djasamen Saragih Regional General Hospital in 2023. Thus Ho is rejected, correlation strength (r) = 0.008. The relationship between the quality of health services and the level of patient satisfaction is in the dissatisfied category. It is recommended that many provide policies through the best programs in terms of quality of health services, especially in terms of satisfaction levels at the HIV/AIDS Outpatient Polyclinic, Djasamen Saragih Regional General Hospital